The Effects of Thawing Methods on Trained Sensory Evaluation of Beef Palatability Traits and Instrumental Measurements of Quality - Lindsey K. Decker; Erin S. Beyer; Michael D. Chao; Morgan D. Zumbaugh; Jessie L. Vipham; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:Using beef strip loins steaks, evaluate six common thawing methods and assess the quality attributes through a trained panelist evaluation and an array of instrumental quality measures. Study Description:Paired Low Choice strip loins (n = 15) were collected from a beef packing facility. The paired loins were fabricated into 1-in steaks and blocked into six blocks of four steaks. Each block was assigned a different thawing method, and each steak within the block a test, then aged 21 days and frozen. Thaw methods consisted of the four USDA-approved thaw methods: refrigerator (REF), cold water (CW), microwave (MIC), cooking from frozen (COOK); and two methods commonly used by consumers: countertop (CT) and hot water (HW). Steaks assigned to REF were thawed in a refrigerator at 34–37°F for 24 hours prior to cooking. Steaks assigned to CW were thawed in individual containers of 34–37°F water for 24 hours prior to cooking. COOK steaks were cooked immediately upon removal from the freezer, while still in a frozen state. CT steaks were thawed at ambient temperature (68°F) for 5 hours. HW steaks were thawed in a sous vide machine set to 104°F for 20 minutes (± 2 minutes). MIC steaks were microwaved at 50% power for 3.5 minutes, flipped, and repeated in a retail microwave. Fifteen trained panels were performed, with eight panelists consuming six samples from the same loin. Each steak was cooked to a peak temperature of 160°F on clamshell style grills. Data were analyzed as a completely randomized block design. Results:As a whole, thawing method had a minimal impact on palatability There were no (P>0.05) differences among thawing methods for initial juiciness, sustained juiciness, connective tissue, pressed juice percentage, L*(lightness), lipid oxidation, Warner-Bratzler shear force and slice shear force. For myofibrillar tenderness, COOK steaks were tougher (P<0.05) than REF and CW. Also, MIC and COOK steaks were lower (P<0.05) than CW and REF steaks for overall tenderness, while all other treatments were similar (P>0.05). The COOK steaks were rated higher (P<0.05) than all other treatments for beef flavor intensity. The MIC steaks had lower (P<0.05) cooked a* (redness) and b* (yellowness) values than REF, HW, and CW steaks, while CT samples had higher (P<0.05) values than COOK and MIC. The MIC steaks had the highest (P<0.05) cook loss, followed by COOK (P<0.05), with all other treatments being similar (MIC>COOK>CT = HN = CW = REF). MIC and HW had a higher (P<0.05) thaw loss than CW, CT, and REF (MIC = HW>CW = CT = REF). Moreover, MIC, COOK, and HW steaks had a higher (P<0.05) percent total moisture loss than REF, CW, and CT. This increase in total moisture loss and thaw loss could indicate a total economic loss of steaks thawed using these methods. Lastly, COOK steaks had higher (P<0.05) cooked expressible moisture than CT, CW, and REF. The Bottom Line:Consumers and food service establishments may use whichever thawing method is the most economical and convenient for them, as thawing method has minimal impact eating quality, although food safety should be the upmost concern.
Keywords: beef; palatability; thawing; trained sensory analysis